Semiotic Analysis of Environmental Signs and Logos: A Saussurean Perspective - Husna Maulida (Paradigma Lingua, 2025)
This study investigates the semiotics of environmental signs and logos through the lens of Ferdinand de Saussure’s semiotic framework, focusing on the interplay between the signifier and the signified. The research employs a qualitative methodology, analyzing the visual and contextual elements of various environmental signs, including traffic symbols, warning signs, and commercial logos. Findings reveal that universally recognized symbols and culturally specific norms significantly enhance the effectiveness of environmental communication. The study underscores the importance of designing contextually relevant signs that resonate with cultural expectations, ensuring clarity and functionality. Additionally, the research highlights the role of logos in branding and identity, emphasizing their contribution to public space dynamics and consumer perception. These insights contribute to a broader understanding of how semiotics facilitates communication and organization in public spaces.